Two-piece hollow bulb obturator after partial maxillectomy on ameloblastoma case - Nova Mayasari; Heriyanti Amalia Kusuma; Endang Wahyuningtyas (Majalah Kedokteran Gigi Indonesia, 2020)
Ameloblastoma often occurs in the mandibular area, but 15 - 20% of ameloblastoma originates from the maxilla. Ameloblastoma lesions in the maxilla can be treated with partial maxillectomy, which produces defects that alter speech, swallowing function, and aesthetic. The role of prosthodontics is needed to rehabilitate the patient’s condition by fabricating an obturator that helps reduce the morbidity of patients. The main problem with the rehabilitation of substantial defects in the maxilla is the weight of the prosthesis, resulting in non-retentive prosthesis. The purpose of this case report was to evaluate the post-treatment of the partial maxillectomy in the case of ameloblastoma with the hollow bulb to rehabilitate the functions of mastication, phonetics, swallowing function, and aesthetic functions.This case report discussed the treatment of a 58-year-old female who undergone partial maxillectomy, has experienced tooth loss in 15, 14, 13, 12, 11, 21, 22, and 23, and had an anterior palate defect due to mass retrieval under the Aramany class VI classification. The chosen treatment was the fabrication of an obturator with the twopiece hollow bulbmade of acrylic resin. The results of the obturator insertion are good retention, stabilization,occlusion, aesthetics, clear phonetic, and the increasing patient’s confidence. The follow-up control after one week showed good retention, stabilization, occlusion, aesthetics, even clearer pronunciation and a good adaptation from the patient. This case report concludes that the two-piece hollow bulb acrylic resin obturator in ameloblastoma case can rehabilitate the maxillary defect post partial maxillectomy to restore masticatory, phonetic, swallowing and aesthetic functions.